Methane trapping in permafrost soils: a biogeochemical dataset across Alaskan boreal-Arctic gradient - Jinhyun Kim; Yongwon Kim; Sungjin Nam; Ji Young Jung; You Jin Kim; Jeong Ho Hwang; Mincheol Kim (Scientific Data)
Abstract Permafrost soils store vast amounts of organic carbon, and their thawing due to climate warming accelerates the release of carbon as methane and carbon dioxide, exacerbating global climate change. Understanding the distribution of greenhouse gases trapped in these soils and predicting their behavior upon thawing is essential for accurately modeling climate feedbacks. This study presents an integrated biogeochemical and microbial dataset from ~1.8 m deep soil cores collected across a 970 km latitudinal gradient in Alaskan permafrost regions, spanning boreal forest and Arctic tundra biomes. This dataset includes vertical profiles of trapped greenhouse gases, their stable isotope signatures, soil physicochemical properties, and the composition and abundance of key methanogenic and methanotrophic genes. These data provide critical insights into methane cycling within permafrost soils in high-latitude ecosystems and contribute to refining the parameterization of biogeochemical processes in climate models, especially in the context of accelerating permafrost thaw.